The Influence of Price and Location on Foreign Tourists' Purchase Interest at Fairfield by Marriott Bali Kuta Sunset Road - Lindasari, Komang Leony; Pitanatri, Putu Diah Sastri; Adyatma, Prastha (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This study aims to determine the effect of price and location on the purchase interest of foreign tourists at Fairfield by Marriott Bali Kuta Sunset Road. The population in this study were foreign tourists who had an interest in staying at Fairfield by Marriott Bali Kuta Sunset Road. The data analysis techniques used in this study were Multiple Linear Regression, t-test, f-test and Determination Coefficient using the SPSS application. Based on the results of the study, it was found that the t-value> t-table = 5.521> 1.660 and the significance value <α = 0.00 <0.05 so it can be concluded that price and location have a positive and significant effect on the purchase interest of foreign tourists at Fairfield by Marriott Bali Kuta Sunset Road. Price and location have a strong influence on the dependent variable, namely the purchase interest of foreign tourists. When price and location have a strong influence, the purchase interest of foreign tourists will increase. The suggestion that can be given by the researcher is that Fairfield by Marriott Bali Kuta Sunset Road is expected to maintain the quality of products and services and maintain security around the hotel location and add shuttle car facilities to attract tourists' purchase interest.